Efectividad del programa educativo " conversando sobre sexualidad" en el nivel de conocimiento de los adolescentes, Trujillo, 2014 - De La Cruz Paucar, Diana Elizabeth (2015)
The study of quasi- experimental was realized during the months of September and December 2014 with the finality to determine the effectiveness of the educational program: Speaking about sexuality in adolescents in his level of knowledge in the Jose Sanchez Carrion Trujillo Emblematic School. The sample consisted of 40 adolescents who met the inclusion criteria. For data collection was used Questionnaire level of knowledge about adolescent sexuality. The information obtained was processed in SPSS version 22 program, statistical analysis was performed with the test "t" Student, the results are presented in graphics and tables of analysis statist, reaching the following conclusions: Before application educational program 70 percent of adolescents obtained a medium knowledge about sexuality, after application of the educational program, 92.5 percent have a very high level. The Program Educative was effective to improve the level of knowledge about sexuality in adolescents who participated in the study by 62.5 percent.